THE EFFECT OF FINANCIAL PERFORMANCE AND MACROECONOMICS ON STOCK PRICES DURING THE COVID-19 PANDEMIC IN PHARMACEUTICAL SUBSECTOR COMPANIES LISTED ON THE INDONESIA STOCK EXCHANGE - Mitha Indrawati; IA Brahmayanti2 (International Conference On Economics Business Management And Accounting (ICOEMA), 2025)
Stock prices hold significant value and serve as one of the indicators of a company’s success. The movement of stock prices is always an interesting subject to project and analyze. During the COVID-19 pandemic, the stock prices of pharmaceutical subsector companies listed on the Indonesia Stock Exchange experienced changes every quarter, from the fourth quarter of 2019 to the third quarter of 2020. This study aims to determine the influence of financial performance and macroeconomic factors on stock prices during the COVID-19 pandemic This study uses a quantitative research method. Data processing techniques involve multiple linear regression analysis using SPSS 22. The data in this study are secondary data, and the research was conducted during the COVID-19 pandemic, specifically from the fourth quarter of 2019 to the third quarter of 2020. The population in this study includes 11 pharmaceutical subsector companies listed on the Indonesia Stock Exchange, while the sample consists of 8 companies selected through purposive sampling. The results of this study indicate that, simultaneously, financial performance measured by Return on Assets, Earnings per Share, Debt to Equity Ratio, and macroeconomics measured by inflation and exchange rates have a significant impact on stock prices. However, on a partial basis, Earnings per Share and inflation have a significant impact on stock prices. Return on Assets, Debt to Equity Ratio, and exchange rates have an insignificant impact on stock prices.